Radiotherapy Quality Assurance in the PORTEC-3 (TROG 08.04) Trial. Issue 3 (March 2022) - Khaw, P.; Do, V.; Lim, K.; Cunninghame, J.; Dixon, J.; Vassie, J.; Bailey, M.; Johnson, C.; Kahl, K.; Gordon, C.; Cook, O.; Foo, K.; et al.
Abstract: Aims: Quality assurance in radiotherapy (QART) is essential to ensure the scientific integrity of a clinical trial. This paper reports the findings of the retrospective QART assessment for all centres that participated in PORTEC-3; a randomised controlled trial that compared pelvic radiotherapy with concurrent chemoradiotherapy to the pelvis followed by adjuvant chemotherapy. The trial showed an overall survival benefit for the addition of the chemotherapy in the management of women with high-risk endometrial cancer. Materials and methods: Clinicians were invited to upload a randomly selected case/s treated at each of the participating sites. Panel reviewers analysed the contours to certify that the target volumes and organ at risk structures were contoured according to guidelines. The results were categorised into acceptable, minor variation, major variation or unevaluable. The radiotherapy plans were dosimetrically evaluated using the well-established Trans-Tasman Radiation Oncology Group (TROG) protocol. Results: Between August 2010 and January 2018, data from 146 patients of 686 consecutively treated patients were retrospectively reviewed. All 16 Australia and New Zealand and 71 of 77 international centres uploaded data for evaluation. In total, 3514 dosimetric and contour variables were reviewed. Of these, 3136 variables were deemed acceptable (89.2%), with 335 minor (9.6%) and 43 major variations (1.2%). Major contour variations included the clinical target volume vaginal vault, clinical target volume parametria and differential planning target volume vault expansion. Conclusion: The results of the QART assessment confirmed high uniformity and low rates of both minor and major deviations in contouring and dosimetry in all sites. This supports the safe introduction of the PORTEC-3 treatment protocol into routine clinical practice. Highlights: Radiotherapy benchmarking reduces the major and minor deviations noted in contouring and dosimetry. Incorporation of a quality QART programme reduces source bias and facilitates adoption of the trial results. Inclusion of real-time QART will improve and standardise international radiotherapy quality in future trials.